Meaning in Life as A Mediator of Associations Between Self-Esteem and Psychological Adjustment Among Middle-Aged Women with Breast Cancer - Cem Soylu; Zehra Uçanok (Psikoloji Çalışmaları)
A growing body of research has clearly demonstrated that meaning in life plays an important role in psychological adjustment in the face of highly stressful life events, such as a cancer diagnosis. This study primarily aims to explore the predictors of meaning in life and the mediating role of the two dimensions of meaning in life (presence of meaning, and search for meaning) on the association between self-esteem and psychological adjustment among middle-aged women diagnosed with breast cancer. In the present study, psychological well-being and psychological distress have been used as indicators of psychological adjustment. The sample consisted of 125 women aged between 40 - 65 (Mage = 52.34, SD = 6.83). Participants completed a battery of self-report questionnaires including the Rosenberg Self-Esteem Scale, Psychological Well-Being Scale, Hospital Anxiety and Depression Scale, Meaning in Life Questionnaire, and Multidimensional Scale of Perceived Social Support. The findings revealed a negative significant relationship between the presence of meaning and the search for meaning. Multiple regression analyses revealed that perceived social support, age, perceived income level, and time since diagnosis positively predicted the presence of meaning and explained 30% of the total variance. On the other hand, perceived social support, age, and the time since diagnosis negatively predicted the search for meaning and explained 34% of the total variance. Moreover, the findings of mediation analysis showed that the presence of meaning in life partially mediates the association between self-esteem and psychological adjustment. In other words, although the predictors of the meaning in life are similar for both dimensions, it was shown that the mediating role of the presence of meaning was stronger than the search for meaning in the relationship between self-esteem and psychological adjustment. Hence, it can be concluded that high self-esteem contributes positively to psychological adjustment by increasing the presence of meaning in the life of middle-aged female cancer patients.